Propagation of hypersonic waves in some viscous fluids - KLESZCZEWSKI, Zygmunt (Archives of Acoustics, 1976)
Taking advantage of Mandelsztam-Brillouin dispersion the velocity of propagation and the absorption coefficient of hypersonic waves at a frequency of 8 GHz have been measured in the following viscous fluids: castor oil, paraffin oil, diethylene glycol, triethylene glycol and polyethylene glycol. The results obtained are discussed on the basis of relaxation theory and ISAKOVICH-CZABAN theory.